2024
DOI: 10.3847/1538-4357/ad206f
|View full text |Cite
|
Sign up to set email alerts
|

UNCOVER: JWST Spectroscopy of Three Cold Brown Dwarfs at Kiloparsec-scale Distances

Adam J. Burgasser,
Rachel Bezanson,
Ivo Labbe
et al.

Abstract: We report JWST/NIRSpec spectra of three distant T-type brown dwarfs identified in the Ultradeep NIRSpec and NIRCam ObserVations before the Epoch of Reionization (UNCOVER) survey of the Abell 2744 lensing field. One source was previously reported as a candidate T dwarf on the basis of NIRCam photometry, while two sources were initially identified as candidate active galactic nuclei. Low-resolution 1–5 μm spectra confirm the presence of molecular features consistent with T dwarf atmospheres, and comparison to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…In this section we briefly describe the UNCOVER survey (Section 2.1 Bezanson et al 2022) and the Micro-Shutter Assembly (MSA)/PRISM spectroscopy and reductions in Section 2.2. Many exciting results have already come from the PRISM spectroscopy of the compact red sources, including a triply imaged z = 7 AGN (Furtak et al 2023b), a broad-line AGN at z = 8.5 (Fujimoto et al 2023a;Kokorev et al 2023), and three brown dwarfs which show similar SEDs as red AGN (Burgasser et al 2024;Langeroodi & Hjorth 2023). We have also reported two z > 12 galaxies (Wang et al 2023), and some of the faintest known targets in the epoch of reionization (Atek et al 2023a).…”
Section: Data Sample and Spectroscopic Follow-upmentioning
confidence: 58%
See 3 more Smart Citations
“…In this section we briefly describe the UNCOVER survey (Section 2.1 Bezanson et al 2022) and the Micro-Shutter Assembly (MSA)/PRISM spectroscopy and reductions in Section 2.2. Many exciting results have already come from the PRISM spectroscopy of the compact red sources, including a triply imaged z = 7 AGN (Furtak et al 2023b), a broad-line AGN at z = 8.5 (Fujimoto et al 2023a;Kokorev et al 2023), and three brown dwarfs which show similar SEDs as red AGN (Burgasser et al 2024;Langeroodi & Hjorth 2023). We have also reported two z > 12 galaxies (Wang et al 2023), and some of the faintest known targets in the epoch of reionization (Atek et al 2023a).…”
Section: Data Sample and Spectroscopic Follow-upmentioning
confidence: 58%
“…Of the 17 targets from L23 with UNCOVER PRISM spectra, 11 have unambiguous evidence for broad emission lines, including three which are multiple images of the same target (Furtak et al 2023b). Three targets do not show clear evidence for broad emission lines, and a further three are brown dwarfs (Burgasser et al 2024). Therefore 11/17 = 65% of the sample are confirmed as broad-line AGN.…”
Section: Yield and Contaminantsmentioning
confidence: 83%
See 2 more Smart Citations
“…At the same time, brown dwarfs also exhibit an upturn in their SEDs starting around 3.0 μm and peaking at ∼4.5 μm, which leads to red LW colors. Brown dwarf candidates have already been identified photometrically due to their peculiar blue-red SEDs using color-color thresholds similar to the ERO selection criteria (e.g., Hainline et al 2023;Holwerda et al 2023;Nonino et al 2023;Wang et al 2023), and recent NIRSpec observations have confirmed the stellar nature of handful of them (Langeroodi et al 2023;Burgasser et al 2024).…”
Section: Brown Dwarf Contaminationmentioning
confidence: 99%